KORELASI INDEKS MASSA TUBUH DENGAN DAYA LEDAK OTOT TUNGKAI PADA USIA 14 - 17 TAHUN PEMAIN SEPAK BOLA SPARTA LIMO DEPOK - Fathur Rohman Agung Wicaksono Putra, (2023)
Background: Football is the most popular team sport in the world because as much as 4% of the world's population is actively involved in this game. The sport of soccer, which is popular with teenagers, requires players to be reliable in mastering the ball and mastering techniques in playing soccer. Another thing that affects the skill of a soccer player is BMI. This is because BMI has a great influence on supporting aspects of playing soccer. One of these aspects is explosive power which has a major influence on soccer movements which are dominated by lower leg movements. Research Purposes: To determine the correlation of body mass index and leg muscle explosive power at the age of 14-17 years of Sparta Limo Depok soccer players. Methods: Thisstudy used a correlational quantitative research design with a cross-sectional approach. With a sample of 80 teenagers who play and practice soccer regularly and with an error of 5%. This research was carried out offline through measuring scales, microtoice and standing board jump tests. Results: After the correlation test, it was found that there was no relationship between Body Mass Index and Limb Muscle Explosive Power, and a correlation coefficient of -0.154 was negative in the same direction. The conclusion of this study resulted that there is no relationship between hypertension and quality of life in the same direction. Keywords: Soccer player; BMI; Explosion power; Scales; microtoice; Standing board jump test